2014
DOI: 10.2521/jswtb.50.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Acids and Amino Acids on the Flocculation Activity of Chitosan-Like Bioflocculant-Producing <i>Citrobacter freundii </i>IFO 13545

Abstract: Citrobacter freundii IFO 13545 produces a chitosan-like bioflocculant (BF) from acetate. The effects of other organic acids (citrate, fumarate, malate, glyoxylate, succinate, and oxaloacetate) as carbon sources on the growth and flocculation activity (FA) of the cultures were investigated. Citrate, fumarate, malate, succinate, or oxaloacetate supported the growth of IFO 13545 as a sole carbon source, but any FA was not detected during the growth on these organic acids. Glyoxylate did not serve as a carbon sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The gram-negative bacteria Citrobacter freundii has also been reported to produce bioflocculant using acetate as a carbon source efficiently. Organics like fumarate, citrate and malate were shown to have a negative impact on bioflocculant production (Kimura et al 2014). Other microalgae studies have reported high flocculation efficiencies by co-cultivating microalgae with other green algae species like Tetraselmis suecica, Ankistrodesmus falcatus and Scenedesmus obliquus (Salim et al 2011).…”
Section: Bioflocculationmentioning
confidence: 99%
“…The gram-negative bacteria Citrobacter freundii has also been reported to produce bioflocculant using acetate as a carbon source efficiently. Organics like fumarate, citrate and malate were shown to have a negative impact on bioflocculant production (Kimura et al 2014). Other microalgae studies have reported high flocculation efficiencies by co-cultivating microalgae with other green algae species like Tetraselmis suecica, Ankistrodesmus falcatus and Scenedesmus obliquus (Salim et al 2011).…”
Section: Bioflocculationmentioning
confidence: 99%